The Influence Of E-Commerce And Brand Image On Purchasing Decisions Scarlett Whitening Product (Survey Of Scarlett Whitening Consumers In Tasikmalaya) - Nurbety, Saifa; Sutrisna, Arga; Wibawa, Gian Riksa (Universitas Dehasen Bengkulu, 2024)
This research aims to determine the influence of e-commerce and brand image on purchasing decisions for Scarlett Whitening product in Tasikmalaya. The analysis technique used was a quantitative method with a survey approach to 100 respondent in Tasikmalaya who had used Scarlett Whitening product. The types of data used are primary data and secondary data. The results of this test show that e-commerce has no significant effect and brand image has a significant effect on purchasing decisions for Scarlett Whitening in Tasikmalaya.